A methodological and theoretical exploration of young children's understanding and experience of stress - Valentine, Althéa Zoë (2012)
Background: Compared with the body of research exploring children's understanding of health and illness, children's understanding of psychological concepts has been less widely studied; although research does indicate that young children may have some understanding of psychological terms such as depression. There is also a paucity of research considering young children's perceptions of stress within their daily lives. This thesis explored children's knowledge, understanding, and experience of stress from 4- to 11-years of age.